Three-point flanged optic piercing intrascleral fixation of multifocal intraocular lenses - Youngsub Eom; Hyun Sun Jeon; Seong-Jae Kim; Dong Hyun Kim; Jong Suk Song; Dooho Brian Kim (Indian Journal of Ophthalmology, 2025)
Purpose: To evaluate the feasibility of a three-point flanged optic piercing intrascleral fixation technique for replacing a dislocated multifocal intraocular lens (IOL). Design: Retrospective cross-sectional study. Methods: In total, 13 eyes from 13 patients with a dislocated single-piece C-loop or double C-loop diffractive multifocal IOL were enrolled to undergo dislocated multifocal IOL replacement through three-point flanged optic piercing 120 degrees apart intrascleral fixation using 7-0 polypropylene sutures at 2.5 mm posterior to the limbus. Preoperative and postoperative uncorrected distance visual acuity (UDVA), postoperative uncorrected intermediate visual acuity (UIVA) at 66 cm, uncorrected near visual acuity (UNVA) at 40 cm, residual refractive errors, and the amount of IOL decentration were evaluated. Results: There were six multifocal IOLs and seven multifocal toric IOLs. There was a notable improvement in visual acuity, with the mean UDVA improving from 0.79 ± 0.72 logMAR preoperatively to 0.06 ± 0.08 logMAR postoperatively (P = 0.004). The mean postoperative UIVA and UNVA were 0.04 ± 0.05 and 0.10 ± 0.12 logMAR, respectively. The mean residual refractive sphere, cylinder, and spherical equivalent were −0.04 ± 0.48 D, −0.29 ± 0.25 CD, and −0.18 ± 0.47 D, respectively. The mean residual cylinder was −0.25 ± 0.25 CD in eyes with multifocal toric IOL fixation. The mean amount of IOL decentration was 0.22 ± 0.05 mm. Conclusion: The three-point flanged optic piercing intrascleral fixation technique for dislocated multifocal IOLs could provide good distance, intermediate, and near vision alongside excellent IOL centration.